2002
DOI: 10.1128/cdli.9.5.1137-1141.2002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Techniques To Detect Cryptic Leishmaniasis in Dogs

Abstract: This study of several techniques for detecting cryptic leishmaniasis in dogs from areas in Spain where Leishmania infantum is highly endemic concludes that immunological techniques (enzyme-linked immunosorbent assay, immunofluorescence antibody test, Western blotting, delayed-type hypersensitivity reaction, and in vitro lymphocyte proliferation assay) do not clearly differentiate between noninfected and infected asymptomatic dogs and that culture and PCR are more reliable diagnostic tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
10

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 26 publications
1
40
0
10
Order By: Relevance
“…The low sensitivity of in vitro culture observed in our study is in correlation with what is found in some studies (Berrahal et al, 1996, Fisa et al, 2001. However, other studies found sensitivity as high as that of PCR in dog blood (Iniesta et al, 2002) or in human blood (Kaouach et al, 2008). This difference can be due to the method used and the local conditions of in vitro culture.…”
Section: Diagnosis Of Canine Leishmaniasismentioning
confidence: 93%
“…The low sensitivity of in vitro culture observed in our study is in correlation with what is found in some studies (Berrahal et al, 1996, Fisa et al, 2001. However, other studies found sensitivity as high as that of PCR in dog blood (Iniesta et al, 2002) or in human blood (Kaouach et al, 2008). This difference can be due to the method used and the local conditions of in vitro culture.…”
Section: Diagnosis Of Canine Leishmaniasismentioning
confidence: 93%
“…The presence of L. infantum kDNA in the blood of most of our patients did not lead to either a cellular or a humoral response in our patients. Surveys conducted to detect cryptic leishmaniasis in dogs also showed a higher prevalence by PCRpositive results than by antibody detection techniques (9,22). Le Fichoux et al (10) suggested that in healthy L. infantum carriers, episodes of parasitemia might be of low intensity and, therefore, a cellular or humoral immune response may not be triggered.…”
Section: Discussionmentioning
confidence: 99%
“…Para o diagnóstico da LVC, as técnicas sorológicas são consideradas rápidas e práticas, mas com sensibilidade variável e especificidade baixa (BADARÓ et al, 1983;INIESTA et al, Tabela 3. Análise comparativa do número (nc) e porcentagens (%) de concordância e índice Kappa (κ) entre as técnicas imunoistoquímica (IMIQ) × ELISA, IMIQ × RIFI, ELISA × RIFI, PCR × IMIQ, PCR × ELSA e PCR × RIFI para diagnóstico de Leishmaniose Visceral em cães naturalmente infectados e classificados em assintomáticos (A), oligossintomáticos (O) e polissintomáticos (P).…”
Section: Grupos (N)unclassified
“…Enquanto os testes sorológicos apresentam mais resultados falso positivos por causa das reações cruzadas com outros patógenos (BADARÓ et al, 1983;INIESTA et al, 2002), os métodos parasitológicos são mais precisos, mas também mais invasivos porque, usualmente, requerem punção de linfonodo periférico ou medula óssea.…”
Section: Introductionunclassified